Unraveling the evolutionary dynamics of toxin-antitoxin systems in diverse genetic lineages of Escherichia coli including the high-risk clonal complexes - Singh, Anuradha; Lankapalli, Aditya Kumar; Mendem, Suresh Kumar; Semmler, Torsten; Ahmed, Niyaz (mBio, 2024)
Escherichia coli is a highly versatile microorganism with a unique ability to survive and persist in varied niches of the human and animal hosts and the environment. While commensal strains of E. coli play a crucial role in preserving and maintaining the balance and function of their community within the gut microflora, pathogenic strains are often implicated in a wide range of infections and outbreaks, posing a serious threat to public health systems. With the increasing burden of highly virulent and antimicrobial-resistant E. coli infections, it is imperative to understand the host-defense mechanisms of bacteria from all possible dimensions. Mobile genetic elements (MGE)-mediated acquisition of genetic material, chromosomal reduction, and genome optimization are three important events that play a significant role in bacterial evolution and enable them to survive in diverse environmental niches. Toxin-antitoxin (TA) systems are genetic elements that help in the maintenance of MGEs and are often associated with stress response phenotypes, including antimicrobial resistance. In this study, large-scale comparative genomics of 950 genomes spanning 19 different sequence types (STs) (eight phylogroups) revealed ST-wide prevalence patterns of TA systems with a median of 23 toxin groups per strain. Our analyses revealed significant genomic reduction in the members of phylogroup B2 (ST131, ST95, ST73, ST12, and ST127) and phylogroup C (ST410) as evident from a diminished toxin repertoire amidst abundant orphan antitoxins. Moreover, our observations also enabled crucial insights into the copy number of toxin groups, the genetic organization of TA operons, and their association with other genetic coordinates (antimicrobial resistance encoding genes/virulence genes/mobile genetic elements). By unraveling the association of the genetic coordinates/STs with the toxin groups, this study significantly boosts our understanding of the functional implications of TA systems in different evolutionary contexts entailing pathogenic Escherichia . Large-scale genomic studies of E. coli provide an invaluable opportunity to understand how genomic fine-tuning contributes to the transition of bacterial lifestyle from being commensals to mutualists or pathogens. Within this context, through machine learning-based studies, it appears that TA systems play an important role in the classification of high-risk clonal lineages and could be attributed to their epidemiological success. Due to these profound indications and assumptions, we attempted to provide unique insights into the ordered world of TA systems at the population level by investigating the diversity and evolutionary patterns of TA genes across 19 different STs of E. coli . Further in-depth analysis of ST-specific TA structures and associated genetic coordinates holds the potential to elucidate the functional implications of TA systems in bacterial cell survival and persistence, by and large.